Effects of exercise and cooling on reproductive efficiency of ewes bred during summer months - Spies, H.G.; Menzies, C.S.; Smith, W.H.; Scott, S.P. (Kansas Agricultural Experiment Station, 2011)
Failure of ewes to conceive during summer is one of the biggest problems affecting the early spring lamb producer. Workers at other stations have reported that 90 F temperatures lowered reproductive performance. This study was designed to determine the effects of forced exercise and temperature on reproductive performance of ewes.
Keywords: Sheep; Reproductive efficiency; Exercise; Cooling